Valuation of provisional and cultural services of a Ramsar site: A preliminary study on Rudrasagar lake, India - Moitree Taran; Sourabh Deb (Center for Journal Management and Publication, 2017)
Rudrasagar lake, a Ramsar site in India offers a variety of ecosystem services. The contribution of Rudrasagar lake to the society has not been estimated so far. The preliminary study aims to provide an economic valuation of the provisional and cultural services of the Rudrasagar lake. Official records of revenue collected by the Tourism Department of Tripura and a socio- economic survey was the source of information used in the economic valuation of the lake. The main provisional services provided by the lake are food (aquatic plants and fishes), fuel wood and timber whereas, the cultural services provided were boat raiding and tourism due to its historical importance. The provisioning and cultural services provided by the Rudrasagar lake are 40810 US and 33929.33 US per year respectively during the period of 2010-2015. The main threats to the wetland identified are increasing silt loads due to deforestation, expansion of agricultural land and land conversion due to population pressure. To alleviate the anthropogenic stress on the lake, better monitoring, planning and management are essential. By proper conservation and management it will be possible to enjoy the provisional and cultural services of the lake in a sustainable way.